Carotid endarterectomy with extended lesion: formation of a new bifurcation according to A.V.Pokrovsky or autoarterial reconstruction according to A.A.Karpenko? - A. N. Kazantsev; K. P. Chernykh; N. E. Zarkua; R. Yu. Leader; K. G. Kubachev; G. Sh. Bagdavadze; E. Yu. Kalinin; T. E. Zaitseva; A. E. Chikin; Yu. P. Linets (Исследования и практика в медицине)
Purpose of the study. Comparison of hospital and long-term results of autoarterial reconstruction of carotid artery bifurcation and the formation of a new bifurcation with an extended atherosclerotic lesion of the internal carotid artery (ICA). Materials and methods. In the period from January 2018 to May 2020, this cohort, comparative, prospective, open-label study included 279 patients with an extended atherosclerotic lesion of the ICA operated on in the Alexandr Hospital. Depending on the implemented strategy of surgical correction, all patients were divided into two groups: group 1 (n=132) — autoarterial reconstruction of bifurcation of the carotid arteries; Group 2 (n=147) — the formation of a new bifurcation. Complications were recorded in the hospital and long-term postoperative periods. The total follow-up period was 16.4±9.3 months. The endpoints of the study were such adverse cardiovascular events as death, myocardial infarction (MI), stroke, thrombosis / restenosis of the anastomosis zone, combined endpoint (death from stroke / IM + IM + stroke). Results. The ICA clamping time in group 1 was 32.6±3.3 minutes, in group 2 – 31.7±3.5 minutes, which did not receive statistically significant differences (р=0.81). In the hospital postoperative period, adverse cardiovascular events were not recorded. In the long-term follow-up, the groups were comparable in the frequency of all complications. Identified lethal outcomes developed as a result of the formation of MI in patients with multiple lesions of the coronary arteries and a history of myocardial revascularization. The likely cause was shunt / stent thrombosis with subsequent coronary insufficiency and an increase in ischemic heart damage. The causes of stroke, recorded in each group in isolated cases, were the presence of atrial fibrillation. Patients did not comply with the recommended regimen of anticoagulant therapy, which provoked the development of cerebral catastrophe. In turn, the identified restenoses of the reconstruction zone were asymptomatic and were also observed in isolated cases in each group in the period 12 months after CEE. Conclusion. Autoarterial reconstruction of carotid bifurcation and the formation of a new bifurcation are comparable in safety and effectiveness methods of surgical treatment of an extended atherosclerotic lesion of the ICA. Operation techniques differ in the choice of an artery that is cut off from bifurcation — the external carotid artery or ICA. Further, the reconstruction progress is absolutely identical. Hospital and long-term follow-up results showed minimal indicators of the development of cardiovascular and hemodynamic changes due to the type of operation. Thus, both reconstruction techniques can be the operation of choice for an extended ICA lesion.